2020
DOI: 10.1155/2020/2120971
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Protects against Ischemia and Reperfusion-Induced Kidney Injury in Rats

Abstract: Acute kidney injury (AKI), a clinical syndrome, is a sudden onset of kidney failure that severely affects the kidney tubules. One potential treatment is dexmedetomidine (DEX), a highly selective α2-adrenoreceptor agonist that is used as an anesthetic adjuvant. It also has anti-inflammatory, neuroprotective, and sympatholytic qualities. The aim of this study was to establish whether DEX also offers protection against ischemia and reperfusion- (I/R-) induced AKI in rats. An intraperitoneal injection of DEX (25 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…A body of evidence suggested that the pathogenesis of sepsis‐induced AKI was thought to be caused by a pro‐inflammatory response 61,62 . Levels of cytokines such as IL‐1β, IL‐6, and TNF‐α have been shown to correlate with the severity and mortality of septic AKI 63,64 . The present study showed that the secretion of pro‐inflammatory cytokines IL‐1β, IL‐6, and TNF‐α was significantly increased in HK‐2 cells after hypoxic treatment.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A body of evidence suggested that the pathogenesis of sepsis‐induced AKI was thought to be caused by a pro‐inflammatory response 61,62 . Levels of cytokines such as IL‐1β, IL‐6, and TNF‐α have been shown to correlate with the severity and mortality of septic AKI 63,64 . The present study showed that the secretion of pro‐inflammatory cytokines IL‐1β, IL‐6, and TNF‐α was significantly increased in HK‐2 cells after hypoxic treatment.…”
Section: Discussionsupporting
confidence: 52%
“…61 , 62 Levels of cytokines such as IL‐1β, IL‐6, and TNF‐α have been shown to correlate with the severity and mortality of septic AKI. 63 , 64 The present study showed that the secretion of pro‐inflammatory cytokines IL‐1β, IL‐6, and TNF‐α was significantly increased in HK‐2 cells after hypoxic treatment. More importantly, lncRNA MALAT1 silencing reduced the levels of IL‐1β, IL‐6, and TNF‐α in HK‐2 cells after hypoxia treatment, while miR‐204 inhibitor had a pro‐inflammatory effect on inflammation.…”
Section: Discussionsupporting
confidence: 49%
“…The pharmacological effects of dexamethasone are concentrated in anti-inflammatory (Yu et al, 2019), anti-endotoxin (Yang et al, 2019), immunosuppressive (Hoppstädter et al, 2019;Kim et al, 2020), andanti-shock (O'Connor et al, 2003). Although some studies have shown that dexamethasone is effective in improving inflammation and regulating immune function (Bao and Dai, 2020;Fang et al, 2021), long-term use of glucocorticoids is associated with a series of side effects, including obesity, hypertension, osteoporosis, etc., (Son et al, 2017;Herrera et al, 2020;Xu et al, 2020) Therefore, it is important to find effective drugs with minimal side effects for the treatment of sepsis associated intestinal mucosal injury.…”
Section: Discussionmentioning
confidence: 99%
“…In models of acute lung injury caused by renal ischemia-reperfusion injury, DEX pre-and posttreatment significantly reduce pulmonary edema and inflammatory response by reducing myeloperoxidase (MPO) activity as well as downregulating intercellular adhesion molecule-1 (ICAM-1) and TNF-α mRNA expression [71,72]. In the rat sepsis model [24], DEX inhibits inflammatory response in the lung by the TLR4/myeloid differentiation factor 88/NF-κB pathway and reduces mortality by activating PI3K/Akt/mTOR pathways.…”
Section: Relieves Inflammation Apoptosis and Oxidative Stress From mentioning
confidence: 99%